2019
DOI: 10.1021/acsabm.9b01006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Enhanced Generation of Reactive Oxygen Species for MRI-Guided Tumor Therapy by the Fe@Fe3O4-Based Peroxidase-Mimicking Nanozyme

Abstract: Reactive oxygen species (ROS)-based tumor therapy is still challenging due to limited ROS-generating efficacy. Herein, we constructed heparin-conjugated Fe@Fe3O4 NPs (Fe@Fe3O4@heparin, denoted as MNPs) as a peroxidase-mimicking nanozyme to generate ROS for tumor therapy through the combination of the ultrasound-stimulated Fenton reaction and the increased concentration of H2O2 by β-lapachone (La) in a tumor. La was first intraperitoneally injected into mice and induced to generate a considerable quantity of H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…However, this descriptor is obviously inapplicable to non-noble metals, which easily induce the dissociation of H 2 O 2 due to their strong reducibility but show no POD-like activities. For monometallic Fe 3 O 4 nanoparticles consisting of both trivalent Fe­(III) and divalent Fe­(II) ions, Chen et al found that the nanoparticles containing more Fe­(II) had stronger POD-like activities . However, this relationship between the Fe­(II) content and POD-like activity cannot be generalized to all iron oxides because ferrous oxide (FeO) nanoparticles consisting entirely of Fe­(II) have lower POD-like activities than Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this descriptor is obviously inapplicable to non-noble metals, which easily induce the dissociation of H 2 O 2 due to their strong reducibility but show no POD-like activities. For monometallic Fe 3 O 4 nanoparticles consisting of both trivalent Fe­(III) and divalent Fe­(II) ions, Chen et al found that the nanoparticles containing more Fe­(II) had stronger POD-like activities . However, this relationship between the Fe­(II) content and POD-like activity cannot be generalized to all iron oxides because ferrous oxide (FeO) nanoparticles consisting entirely of Fe­(II) have lower POD-like activities than Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Natural enzymes, one of the most potent biocatalysts with high catalytic activities and substrate specificity, play an essential role in industrial, medical, and biological fields. [1,2] However, the inherent deficiencies of natural enzymes, such as high cost of fabrication and purification, low operational stability, (e.g., pH value, [25] oxygen content, [26] and redox conditions [27,28] ) or external stimuli (e.g., light, [29][30][31][32][33] ultrasound, [34,35] and X-rays [36] ), which result in unsatisfactory catalytic performance and selectivity toward a particular catalytic reaction. Moreover, the size, crystal structure, elemental composition, and surface status of diverse Enz-Cats are of great significance in the adjustment of catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although some developed Enz‐Cats have exhibited efficient in vitro activities, the catalytic performances and selectivity in diverse physiological environments are still vital considerations during the exploration of their further application in biomedical areas. [ 22–24 ] Furthermore, the inherent physicochemical characteristics of these Enz‐Cats may yield multiple catalytic reactions, such as generating or scavenging reactive oxygen species (ROS) under internal microenvironments (e.g., pH value, [ 25 ] oxygen content, [ 26 ] and redox conditions [ 27,28 ] ) or external stimuli (e.g., light, [ 29–33 ] ultrasound, [ 34,35 ] and X‐rays [ 36 ] ), which result in unsatisfactory catalytic performance and selectivity toward a particular catalytic reaction. Moreover, the size, crystal structure, elemental composition, and surface status of diverse Enz‐Cats are of great significance in the adjustment of catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…These peculiar features in the TME can thus be exploited as a strategy for tumor-specific treatment by introducing a peroxidase (POD)-mimicking nanozyme [ 5 ]. In the presence of a POD-mimicking nanozyme, H 2 O 2 can be decomposed into hydroxyl radicals (•OH) under acidic conditions [ 6 ]. The produced •OH is a highly toxic substance that can attack and oxidize most organic molecules (cell proteins, cell proteins, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, glycolysis is inhibited and the pH is controlled at approximately 7.4 [ 10 , 11 ]. The catalytic performance of POD-mimicking nanozymes is acidic pH-triggered [ 6 ]. POD-like catalytic activities are activated in the acidic TME to generate highly toxic •OH and cause tumor cell death while this does not occur in the neutral pH environment of normal tissues, leaving the normal cells unharmed.…”
Section: Introductionmentioning
confidence: 99%